CAPITAL INFLOWS, FINANCIAL DEEPENING AND ECONOMIC GROWTH NEXUS: THE MISSING LINK - Amassoma Ditimi; Azeez Oluwatobiloba (Economic Review)
The purpose of this study was to investigate direct effects of capital inflow, financial deepe-ning on economic growth in Nigeria due to diverse contentions it stirred among researchers from 1981 to 2018 using the Autoregressive Distributive Lag (ARDL) co-integration approach. The findings from the study showed the existence of a long-run relationship between foreign capital inflows and economic growth in Nigeria. Furthermore, the ARDL regression estimate re-sults pointed that foreign direct investment (FDI), foreign aids (FA) and financial development (FD) have a positive and significant impact on economic growth, while on the contrary, remittances exerted a negative and insignificant relationship on economic growth. Also inflation and exchange rate results showcased a negative impact on economic growth. Based on the findings of this study, we conclude that capital in-flows (FDI, & FA) positively impact the Nigerian economy both in the short run and long-run within the study period via sound financial deepening, thus concluding that capital inflows are a potential driver of economic growth in Nigeria. Consequently, the study recommends that the central bank should employ a more restrictive monetary policy to suppress the ad-verse effect that could emanate from inflationary pressure which can distort proper channeling of capital inflows into the country.